Pendampingan Budidaya Pisang Berkelanjutan dan Manajemen Hama Penyakit di Sindangsari Kabupaten Serang - Maryani Nani; Ratih Kusumawardani; Fajarudin Ahmad (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Banana is a native fruit of Indonesia, grown in all of the Indonesian archipelagos. Most of the national banana production was produced by small-scale and household farmers. Banten is the fifth largest province for national banana producers. Nevertheless, no region was developed only for bananas as the main crop. Pengabdian Kepada Masyarakat program aimed to give knowledge and guidance in sustainable banana cultivation and pest disease management on the banana to Farmers at Desa Sindangsari Banten. It is also the initial program of Universitas Sultan Ageng Tirtayasa to create a banana village in Banten. The program started with a survey of the socio-economy of people in the village, identification of local banana varieties, and pest disease incidence of bananas on the farm. Then, a Focus group discussion on sustainable banana cultivation and pest disease management was conducted, followed by a demonstration of how to plant bananas in good practice. At the end of the program, farmers were given two commercial varieties, Cavendish and Barangan, to be grown on their farms. Farmers follow the discussion enthusiastically, asking questions and describing the current state of their banana cultivation. Sustainable banana cultivation practices could be used in the village to improve the quality and production of household farmers' bananas. Thus, it will increase the value of the banana in the market and raise the farmers' income. Finally, it will promote bananas as the leading local commodity and make Sindangsari a banana village in Banten.